2022
DOI: 10.1002/anie.202112925
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating the Mechanisms of Action of Ferroptosis and the Photothermal Effect for Cancer Theranostics

Abstract: Combination therapy based on different mechanisms of cell death has shown promise in tumor therapy. However, when different modalities are integrated, the maximum synergy of the therapeutic effects is often lacking in the design. Herein, we report a cancer theranostic nanomedicine formula developed by considering the mechanisms of action of ferroptosis and the photothermal effect in combination therapy. The croconaine molecule was encapsulated as both a photothermal converter and an iron‐chelating agent with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 51 publications
0
60
0
Order By: Relevance
“…A similar phenomenon was also observed in the oligomycin-treated HeLa cells (Figure S20). The response of the nucleus and cytoplasm to oligomycin may be related to the “self-protection” of the cell itself . It is known that the replication and transcription of DNA occurred in the nucleus and is associated with cell multiplication.…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon was also observed in the oligomycin-treated HeLa cells (Figure S20). The response of the nucleus and cytoplasm to oligomycin may be related to the “self-protection” of the cell itself . It is known that the replication and transcription of DNA occurred in the nucleus and is associated with cell multiplication.…”
Section: Resultsmentioning
confidence: 99%
“…After 14 days, the tumors, hearts, livers, spleens, lungs, and kidneys were executed and removed. Tumor volumes were calculated according to eqn (5), where L, W and V are the length, width and volume of the tumor, respectively.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…Traditional treatments such as chemotherapy, surgery and radiation therapy suffer from large trauma, high toxicity and side effects and drug resistances, compelling human beings to search for new treatments constantly. Photodynamic therapy (PDT), [1][2][3] photothermal therapy (PTT) 4,5 and chemodynamic therapy (CDT) 6,7 have been the newly developed methods for cancer therapy in recent years. Both PDT and PTT are light-responsive therapies, with the former producing singlet oxygen to kill cancer cells and the latter using the high temperature generated by the photothermal effect to kill cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ferroptosis, a new type of iron-dependent programmed cell death featured as the peroxidation of unsaturated fatty acid on the cell membrane, is an ideal candidate for the combination with PTT. On the one hand, ferroptosis can suppress the expression of heat shock proteins (HSPs) to improve the PTT efficiency, on the other hand, PTT can promote the ferroptosis achieving a synergistic effect [17][18][19][20] . The main mechanism of ferroptosis is related to the imbalance of cellular redox homeostasis including cellular GSH depletion or ROS accumulation 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, ferroptosis can suppress the expression of heat shock proteins (HSPs) to improve the PTT efficiency, and on the other hand, PTT can promote ferroptosis achieving a synergistic effect. [17][18][19][20] The main mechanism of ferroptosis is related to the imbalance of cellular redox homeostasis including cellular GSH depletion or ROS accumulation. 21,22 Fortunately, our group has previously observed that the CTCs containing thiol-sensitive acceptors not only possessed absorption in the NIR-II region but also showed GSH depletion induced ferroptosis, which can enhance antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%